REVITALIZATION AS A COMPONENT OF URBAN STRATEGY - Sych, Olga (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2020)
Revitalization is a key challenge of modern city that requires an integrated approach. This is not only the preservation of monuments, the reconstruction of old houses or fragments of urban space, but a process, that is characterized by comprehensiveness and long duration, the main purpose of which is primarily economic recovery combined with measures to address social and environmental problems. The task of this process is to guarantee the development of cities. Revitalization means the release of degraded (or depressed) areas from the crisis through projects that integrate actions for the well-being of the local community, space and local economy, territorially concentrated and carried out in cooperation with the local community.The elaboration of the legislation in the field of regional policy allowed to state that at present there are no strategic documents that would cover the development of cities and include the revitalization program as a component that should become the main axis of the whole strategy. The glossary proposed in the study defines the main terms of revitalization and outlines the difference between the revitalization program and the regional development program and can be used in the territorial development strategies. The success of the revitalization program requires high-quality legal tools, consolidation at the legislative level, which will clearly define the conditions for the creation of such programs, as well as guarantee funding for the revitalization program in accordance with the development strategies of the city or region. The revitalization program as a key component of the territorial development strategy should contain a specific goal, outline the scale of its implementation, give a detailed description of the tools and financial support, as well as have broad public discussions and the involvement of all stakeholders in the implementation of the program. To increase the effectiveness of revitalization programs it is necessary to improve legal regulation; ensure consistency of revitalization processes not only with development strategies, but also with spatial policy; create a set of financial instruments to provide local governments with diversified financial resources; to guarantee legal and financial security of revitalization measures.